Analisis Makna Pesan Simbolik Penyandang Oligodaktili Dusun Ulutaue di Kabupaten Bone - Ismi Amir Ismi; Andi Alimuddin Unde; Tuti Bahfiarti (LONTAR: Jurnal Ilmu Komunikasi, 2022)
ABSTRACT People with oligodactyly are humans who have less than five fingers and toes. This deficiency is formed since their birth. This study involved five informants from Ulutaue Hamlet, Bone Regency of South Sulawesi Province, Indonesia. People with oligodactyly usually get the nicknames "crab man", "disgusting person", "mapakka finger". In addition to verbal forms, people with oligodactyly also receive non-verbal treatment. Hence, it makes them feel ashamed, heads down and offended. Behind those non-verbal ridicules, people with oligodactyly have non-verbal communication between each other to be used as defense or protection against strangers. Based on these conditions, this research entitled "Analysis of the Meaning of Symbolic Messages for Oligodactyly Persons in Ulutaue Village in Bone Regency". This type of research uses qualitative research methods, ethnographic studies of communication with the aim of describing, analyzing, and explaining the communication behavior of a group of people with oligodactyly. The results of this research concluded that people with oligodactyly have special beliefs about "ade' tomatoa riolo" means the culture of the previous people have an effect on their survival. Departing from this understanding, the oligodactyly group believes that all of this cannot be separated from the existence of a great power that controls everything.